Regulation of Chondrocyte Metabolism and Osteoarthritis Development by Sirt5 Through Protein Lysine Malonylation - Liu, Huanhuan; Binoy, Anupama; Ren, Siqi; Martino, Thomas C.; Miller, Anna E.; Willis, Craig R. G.; Veerabhadraiah, Shivakumar R.; Bons, Joanna; Rose, Jacob P.; Schilling, Birgit; Jurynec, Michael J.; Zhu, Shouan (Arthritis & rheumatology (Hoboken, N.J.), 2025)
Objective Chondrocytemetabolic dysfunction plays an important role in osteoarthritis (OA) development during aging and obesity. Protein posttranslational modifications (PTMs) have recently emerged as an important regulator of cellular metabolism. We aim to study one type of PTM, lysine malonylation (MaK), and its regulator sirtuin 5 (Sirt5) in OA development. Methods Human and mouse cartilage tissues were used to measure SIRT5 and MaK levels. Both systemic and cartilage‐specific conditional knockout mouse models were subject to high‐fat diet treatment to induce obesity and OA. Proteomics analysis was performed in Sirt5−/− and wild‐type chondrocytes. SIRT5 mutation was identified in the Utah Population Database. Results We found that SIRT5 decreases while MaK increases in the cartilage during aging. A combination of Sirt5 deficiency and obesity exacerbates joint degeneration in a sex‐dependent manner in mice. We further delineate the malonylome in chondrocytes, pinpointing MaK's predominant impact on various metabolic pathways, such as carbon metabolism and glycolysis. Lastly, we identified a rare coding mutation in SIRT5 that dominantly segregates in a family with OA. The mutation results in substitution of an evolutionally invariant phenylalanine to leucine (F101L) in the catalytic domain. The mutant protein results in a higher MaK level and decreased expression of cartilage extracellular matrix genes and upregulation of inflammation‐associated genes. Conclusion We found that Sirt5‐mediated MaK is an important regulator of chondrocyte cellular metabolism, and dysregulation of Sirt5‐MaK could be an important mechanism underlying aging‐ and obesity‐associated OA development.